2018
DOI: 10.1016/j.triboint.2018.06.034
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of surface texturing and DLC coating on the functional properties of internal combustion engines

Abstract: A reduction in frictional loss is an important aspect of efficiency in high-performance internal combustion engines. This can be achieved by the well-designed surface texturing of the cylinder bore, which can reduce friction at the ring/bore interface. In this work, dimples were created using plastic deformation on the cylinder surfaces of high-performance motorcycle engines. Prior to texturing, these cylinders had Nikasil coating. One cylinder was subjected to the deposition of DLC coating and then surface te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…They evidenced a coefficient of friction that decreased with increasing dimple density, probably because of wear debris trapping. Koszela et al [19] investigated the combined effect of surface texturing and DLC coating on the functional properties of internal combustion engines. They found that cylinder texturing typically led to a decrease in resistance to sliding movement following an increase in the amount of lubricants in dimples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They evidenced a coefficient of friction that decreased with increasing dimple density, probably because of wear debris trapping. Koszela et al [19] investigated the combined effect of surface texturing and DLC coating on the functional properties of internal combustion engines. They found that cylinder texturing typically led to a decrease in resistance to sliding movement following an increase in the amount of lubricants in dimples.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results showed that laser-textured surfaces significantly reduced the wear volume by up to 57%, especially for surface patterns with micro-grids. Moreover, in most of the studies, the surface was first textured by a laser and then coated; however, this led to a modification of the substrate properties due to the interaction with the laser beam [17][18][19][20][21][22][23][24]. On the contrary, works where LST was designed after the coating realized texture that was thicker than the coating depth [16].…”
Section: Introductionmentioning
confidence: 99%
“…Correlating experimental parameters of DLC film deposition with the resultant chemical and physical film properties is an ongoing task [10][11][12][13][14] that has to consider the specifics of the preparation method and the intended application. In general, for the sample preparation methods that use a gaseous precursor, the hydrogen content of the films can be influenced by the hydrogen to carbon ratio of the precursor gas (e.g., CH 4 , C 2 H 4 , C 7 H 8 or C 2 H 2 ) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Internal combustion engine (ICE) is the most widely used technology in the existing transportation sector that utilizes oil and natural gas as fuel [9][10][11][12][13][14]. Greenhouse gas emissions, depletion of the ozone layer, global warming, air, land, and water etc.…”
Section: Introductionmentioning
confidence: 99%